Asymmetrical Trusted Technology Networks in Developing Economies: A Case Study on Critical Infrastructure in Bhutan. - Pradhan, Pratima; Subba, Bal Kumar; Jamtsho , Thinley; Ghimiray, Ganga Ram; Cook, David M (Bhutan Journal of Research and Development, 2022)
Developing Nations are subject to amplified challenges in terms of the integration of technology, and the exposure to non-domestic opportunism from larger neighboring economies. These challenges are recognizable as asymmetrical differences between what is seen as the normative list of critical infrastructures, and the specialisms that can dominate an emerging economy with early maturity technology networks. This paper discusses the case of Bhutan and demonstrates the need for strengthened approaches to trusted networks to ensure the reliability and continuity of the Nation’s critical infrastructures. The paper also links the importance of trusted information sharing networks as part of an overarching technology strategy that protects the Gross National Happiness of the nation.